A Study of Selected-Response Type Assessment (MCQ) and Essay Type Assessment Methods for Engineering Students - Dwivedi, Chintan (Journal of Engineering Education Transformations, 2019)
In the field of education, students’ assessment provides important data on the knowledge, skill, attitudes, and beliefs of students which are used to refine programs and improve student learning. With the help of assessment data, a teacher can track students’ progress, plan his/her lessons more effectively and can also motivate his/her students by providing an accurate measure of his/her progress. Assessment can be done by using many methods such as multiple-choice question-based test and essay or short answer type test, etc.Whichever assessment method is used, it should enhance student learning in relation to educational goals. Assessment should correctly evaluate students’ performance against curricular goals. The present research paper analyzes the two popular methods of assessment in India which are Essay/short answer type assessment and Multiple-choice question-based assessment. A small study was conducted on 108 students of Bachelor of Technology 8th Semester (IV Year) in order to investigate the two methods. The group of students was examined by using Essay type method and MCQ type method in TCIE-1 and TCIE-2 respectively for the same subject which is power system design.Wilcoxon signed rank test was applied using MATLAB to test the hypothesis of significant difference between scores of students in these two assessments.Moreover, correlation coefficient was also calculated to prove that students require a different skill set to secure good marks in these two methods. So, these two methods should be used to address different assessment purposes.